2002
DOI: 10.1063/1.1498874
|View full text |Cite
|
Sign up to set email alerts
|

Improved dc characteristics of AlGaN/GaN high-electron-mobility transistors on AlN/sapphire templates

Abstract: High-electron-mobility transistors (HEMTs) have been demonstrated on both AlN/sapphire templates and sapphire substrates, and the dc characteristics of the fabricated devices were examined at room temperature. Better dc characteristics with high extrinsic transconductances and drain current densities were observed in the HEMTs grown on AlN/sapphire templates when compared with the HEMTs on sapphire substrates. Extrinsic transconductances of 214 and 137 mS/mm for Wg/Lg=15/2 μm HEMTs on AlN/sapphire templates an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
43
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 14 publications
4
43
0
Order By: Relevance
“…The advantages of using an AlN epitaxial layer as a template for defect density reduction of the subsequent AlGaN layers have been demonstrated in several previous experiments [15,16]. After optimization, X-ray symmetric diffraction (0 0 0 2) revealed narrow full width at half maximum (FWHM) for both rocking and o À 2y scan peaks: 323 arc s for rocking scan and 298 arc s for o À 2y scan, respectively.…”
Section: Resultsmentioning
confidence: 97%
“…The advantages of using an AlN epitaxial layer as a template for defect density reduction of the subsequent AlGaN layers have been demonstrated in several previous experiments [15,16]. After optimization, X-ray symmetric diffraction (0 0 0 2) revealed narrow full width at half maximum (FWHM) for both rocking and o À 2y scan peaks: 323 arc s for rocking scan and 298 arc s for o À 2y scan, respectively.…”
Section: Resultsmentioning
confidence: 97%
“…On the other hand, it was reported that high crystalline quality epitaxial AlN films grown on sapphire substrate at high temperature are promising template for GaN epitaxial growth [1]. The superior performance of GaNbased devices, high electron mobility transistor (HEMTs), grown on epitaxial AlN/sapphire template has also been shown [2][3][4]. Besides, an understanding of defects in these materials is essential for improving material quality and device performance.…”
mentioning
confidence: 98%
“…[1][2][3][4][5] In recent decades, much effort has been directed toward the synthesis of pnictide-and chalcogenide-based inorganic semiconductor materials such as GaN, [6] SiC, [7] ZnO 2 , [8] and SnO 2 [9] because of their comparatively wide HOMO-LUMO gaps. There has been little investigation, however, of the photoelectronic properties of molecular solids.…”
mentioning
confidence: 99%